2010
DOI: 10.3819/ccbr.2010.50001
|View full text |Cite
|
Sign up to set email alerts
|

Time and Associative Learning.

Abstract: In a basic associative learning paradigm, learning is said to have occurred when the conditioned stimulus evokes an anticipatory response. This learning is widely believed to depend on the contiguous presentation of conditioned and unconditioned stimulus. However, what it means to be contiguous has not been rigorously defined. Here we examine the empirical bases for these beliefs and suggest an alternative view based on the hypothesis that learning about the temporal relationships between events determines the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
186
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(198 citation statements)
references
References 108 publications
9
186
1
Order By: Relevance
“…The idea is that each and every event and action, or elapsed time between two events, is automatically encoded and stored in memory together with its intrinsic dynamical property (duration), relative to its initial internal or/and external encoding context (see Balsam, Drew & Gallistel, 2010). According to the theory of grounded time (for a further presentation see Droit-Volet, in press since 2010), directly derived from the theories of grounded cognition, sometimes also called embodied cognition (Barsalou, 1999(Barsalou, , 2008Niedenthal, 2007), some temporal judgments are based on changes in emotional and sensory-motor states, in bodily states, that are experienced and/or re-experienced/reactivated during the judgment process (Chambon, Droit-Volet & Niedenthal, 2008;Chambon, Gil, Niedenthal & Droit-Volet, 2005;Effron, Niedenthal, Gil & Droit-Volet, 2006).…”
Section: Embodiment Of Timingmentioning
confidence: 99%
“…The idea is that each and every event and action, or elapsed time between two events, is automatically encoded and stored in memory together with its intrinsic dynamical property (duration), relative to its initial internal or/and external encoding context (see Balsam, Drew & Gallistel, 2010). According to the theory of grounded time (for a further presentation see Droit-Volet, in press since 2010), directly derived from the theories of grounded cognition, sometimes also called embodied cognition (Barsalou, 1999(Barsalou, , 2008Niedenthal, 2007), some temporal judgments are based on changes in emotional and sensory-motor states, in bodily states, that are experienced and/or re-experienced/reactivated during the judgment process (Chambon, Droit-Volet & Niedenthal, 2008;Chambon, Gil, Niedenthal & Droit-Volet, 2005;Effron, Niedenthal, Gil & Droit-Volet, 2006).…”
Section: Embodiment Of Timingmentioning
confidence: 99%
“…Gibbon & Balsam, 1981;Gallistel & Gibbon, 2000; see also Balsam & Gallistel, 2009;Balsam, Drew & Gallistel, 2010). Information about the rate of US delivery during the CS, and also in the CS's absence, is computed, and the comparison between these two values indicates the likelihood that the CS signals the US.…”
Section: Non-associative Accounts Of Conditioning: Time-accumulation mentioning
confidence: 99%
“…A theory that does this can then serve as a guide to what to look for in the brain. Many aspects of the behavior produced by the Pavlovian and operant conditioning protocols commonly used to study associative learning have been shown to depend on differences and ratios between intervals demarcated by different events and experienced at different times in the course of training (Gallistel 1990, Barnet and Miller 1996, Barnet, Cole et al 1997, Savastano and Miller 1998, Arcediano, Escobar et al 2003, Balsam and Gallistel 2009, Balsam, Drew et al 2010). …”
Section: Introductionmentioning
confidence: 99%